2018
DOI: 10.1038/s41467-018-05573-y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping molecular landmarks of human skeletal ontogeny and pluripotent stem cell-derived articular chondrocytes

Abstract: Tissue-specific gene expression defines cellular identity and function, but knowledge of early human development is limited, hampering application of cell-based therapies. Here we profiled 5 distinct cell types at a single fetal stage, as well as chondrocytes at 4 stages in vivo and 2 stages during in vitro differentiation. Network analysis delineated five tissue-specific gene modules; these modules and chromatin state analysis defined broad similarities in gene expression during cartilage specification and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 65 publications
5
86
0
Order By: Relevance
“…NLGN1 encodes neuroligin 1, which is a postsynaptic adhesion molecule involved in the regulation of glutamatergic transmission. More recently it was shown that NLGN1 is expressed during chondrogenesis and marks cellular identity of articular chondrocytes 27…”
Section: Discussionmentioning
confidence: 99%
“…NLGN1 encodes neuroligin 1, which is a postsynaptic adhesion molecule involved in the regulation of glutamatergic transmission. More recently it was shown that NLGN1 is expressed during chondrogenesis and marks cellular identity of articular chondrocytes 27…”
Section: Discussionmentioning
confidence: 99%
“…However, functional studies are required to elucidate the molecular mechanism whereby these variants increase OA risk. Integrating genetic variants with genome-wide datasets of cartilage AI 52 , chromatin states 57 and open chromatin regions 77 will inform functional analyses of these loci. RNA sequencing studies have characterised new chondrocyte subtypes 60 and systematically identified all miRNAs 53 , lncRNAs 54 and circRNAs 73 present in OA cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of novel human skeletal transcriptomic analyses were published the last year, including RNAseq based datasets of OA cartilage 52e55 , timecourse analysis of in vitro chondrogenesis 56,57 and profiling of human foetal chondrocytes, myoblasts, osteoblasts, ligamentocytes and tenocytes 57 . Such RNAseq datasets generate a huge treasure trove of gene expression information, although the published studies typically focus only on a small subset of the data, with the remaining data either relegated to supplemental files or not provided.…”
Section: Transcriptomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in mammals only RSPO2 , and not RSPO3 , seems to be implicated in AER function [4244]. Similarly, species-specific modifications in the gene regulatory networks driving skeletal cell type maturation have been reported [45, 46]. Together with recent scRNA-seq studies in other vertebrate model organisms [30, 47, 48], our dataset now opens new avenues for a comprehensive assessment of molecular similarities and divergences in patterning-relevant cell populations of the developing limb, across all major tetrapod clades.…”
Section: Discussionmentioning
confidence: 99%